Pedagogical Interventions through Software Tools in Postgraduate Engineering Programme - Tapaskar, R. P.; Revankar, P. P.; Gorwar, M. B.; Hosmath, R. S. (Journal of Engineering Education Transformations, 2018)
Educational institutes have been practicing the proprietary software extensively with a profound impression that only the proprietary software can accomplish the educational requirements leading anticipated outcomes. In fact, open source software (OSS) tools can provide the indispensable flexibility to combine languages, scripts, learning objects and lesson plans, effectively, without the cost and rigidity of proprietary software and other added benefits. The present pedagogical intervention highlights the idea computational tools and software in postgraduate engineering curriculum in Energy Systems Engineering. The proposed work on the available options which can potentially employ Software tool with benefits to educational institutes and student's community. The outcomes of implementing these pedagogical strategies have shown the accelerated learning skills of the students in the engineering discipline.